A review of the auditory-gut-brain axis - Graham, Amy S.; Ben-Azu, Benneth; Tremblay, Marie-Ève; Torre, Peter; Senekal, Marjanne; Laughton, Barbara; van der Kouwe, Andre; Jankiewicz, Marcin; Kaba, Mamadou; Holmes, Martha J. (Frontiers in Neuroscience, 2023)
Hearing loss places a substantial burden on medical resources across the world and impacts quality of life for those affected. Further, it can occur peripherally and/or centrally. With many possible causes of hearing loss, there is scope for investigating the underlying mechanisms involved. Various signaling pathways connecting gut microbes and the brain (the gut-brain axis) have been identified and well established in a variety of diseases and disorders. However, the role of these pathways in providing links to other parts of the body has not been explored in much depth. Therefore, the aim of this review is to explore potential underlying mechanisms that connect the auditory system to the gut-brain axis. Using select keywords in PubMed, and additional hand-searching in google scholar, relevant studies were identified. In this review we summarize the key players in the auditory-gut-brain axis under four subheadings: anatomical, extracellular, immune and dietary. Firstly, we identify important anatomical structures in the auditory-gut-brain axis, particularly highlighting a direct connection provided by the vagus nerve. Leading on from this we discuss several extracellular signaling pathways which might connect the ear, gut and brain. A link is established between inflammatory responses in the ear and gut microbiome-altering interventions, highlighting a contribution of the immune system. Finally, we discuss the contribution of diet to the auditory-gut-brain axis. Based on the reviewed literature, we propose numerous possible key players connecting the auditory system to the gut-brain axis. In the future, a more thorough investigation of these key players in animal models and human research may provide insight and assist in developing effective interventions for treating hearing loss.